Pemanfaatan Media Aplikasi Flashcards Maker dalam Meningkatkan Kemampuan Membaca Al Qur`an Siswa Kelas VII SMPIT Daarul Hikmah Boarding School Bontang Lestari Tahun Pelajaran 2023/2024 - Akbar, Muhammad Rafli Alif; Husain, Ahmadi (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
This research discusses the use of the Flashcards Maker application in improving the ability to read the Qur'an. The aim of this research is to find out and understand how to use the Flashcards Maker application to improve the ability to read the Qur'an. The method used is qualitative. The research subjects were class VII students of SMPIT Daarul Hikmah Boarding School Bontang Lestari. Data collection techniques using observation, interviews and documents. Data analysis uses data reduction, presentation and conclusions. The research results show that the use of the Flashcards Maker application can increase students understanding of the concept of reading the Qur'an because it provides new colors in the era of digitalization with the addition of audio and visuals which help students remember and understand the material provided. This application proves its usefulness in growing students interest in learning the Qur'an. From the research data, there was an increase in the reading volume achievements of students who used the Flashcards Maker application. It can be concluded that the use of the Flashcards Maker application in learning the Qur'an has a positive impact and makes learning more effective, efficient and enjoyable so that it can improve students' ability to read the Qur'an.